Evolution of Salary Differences between Men and Women in Six Latin american Countries (2004)
This study investigates the evolution of salary differences and other aspects related to the labor activities of men and women in latin America. The analysis compares six countries - Argentina, Brasil, Colombia, Costa Rica, Honduras, and Uruguay - which were selected based on the information available during the study period.